Development-Based Human Rights? : The Normative Endeavors of China in the United Nations Human Rights Council - Ylinen, Hanna-Mari (My University, 2024)
In recent years, China has ramped up its actions in multilateral international organizations such as the United Nations. Through these organizations, it has a chance to use its normative power to diffuse, alter, and finally institutionalize its preferred norms. This research focuses on China’s actions in the United Nations Human Rights Council (HRC). It aims to uncover the ways in which China is altering global human rights norms through the HRC resolutions it is a main sponsor of, focusing on the development-related resolutions entitled “Contribution of Development to the Enjoyment of All Human Rights”. Through these resolutions, China promotes its view of the connection between development and human rights. The research is conducted through a qualitative thematic analysis focusing on the four HRC resolutions adopted between 2017 and 2023. The dataset consists of all four resolutions with their draft versions, more extended reports related to the resolutions, and speeches from both China’s and the co-sponsor countries’ delegations given during the resolutions’ voting situations. The key findings include four themes identified from the dataset: Development-based approach to human rights, Common development, Global prosperity, and People-centred development. These four themes reflect both the normative changes China is promoting and the issues that co-sponsors of the resolutions decided to support. The key findings conclude that China is using a broadening strategy to broaden the widely accepted right to development norm and stress the priority of development over other human rights. The broadening of the norm can, in turn, weaken other norms, such as individual rights and the indivisibility and universality of all human rights. The research provides an in-depth analysis of the processes surrounding the development related HRC resolutions China is the main sponsor of while contributing to the overall research field that considers China a global normative leader.
Keywords: China, human rights, development, norms, normative power, United Nations Human Rights Council, multilateral organizations